Angus and Sadie. - Voigt, Cynthia; a Leigh, Tom, |e ill (New York : HarperCollins, 2005)
Angus and Sadie, two siblings that are of mostly border collie heritage, are adopted by a young couple and start living on a Maine farm, where they begin to learn sheep herding and come to appreciate how they are different from each another.
3-6
Keywords: Border collie--Juvenile fiction; Border collie--Fiction.; Dogs--Fiction; Farm life--Maine--Fiction.; Maine |v Fiction